An Optimal Ninth Order Iterative Method for Solving Non-Linear Equations - Kumar Palli, Rajesh; Sandeep Kumar Mylapalli, Mani; Sri, Ramadevi (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we suggest and analyze a new ninth-order three-step iterative method for solving non-linear equations. This method is compared with the existing ones through some numerical examples to exhibit its superiority.